2014
DOI: 10.1111/pan.12574
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine premedication reduces minimum alveolar concentration of sevoflurane for laryngeal mask airway insertion and emergence delirium in children: a prospective, randomized, double‐blind, placebo‐controlled trial

Abstract: Intranasal dexmedetomidine premedication produces a dose-dependent decrease in the minimum alveolar concentration for laryngeal mask airway insertion of sevoflurane and emergence delirium in the PACU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 25 publications
3
68
1
Order By: Relevance
“…Recovery time (defined as the time from the end of operation to spontaneous eye opening or response to verbal command) and extubation time (defined as the time from the completion of operation to extubation) was evaluated and recorded. Objective pain score (OPS) (as shown in Table 1) [22,23] was used for the evaluation of pain degree, and the PAED scale (as shown in Table 2) [2427] and CPS (as shown in Table 3) [2830] was employed to assess POED at the time points of 0, 5, 15, 30, 45, and 60 minutes after transfer into the PACU. One parent or guardian met the child on arrival in the recovery area and the child was allowed to regain consciousness undisturbed.…”
Section: Methodsmentioning
confidence: 99%
“…Recovery time (defined as the time from the end of operation to spontaneous eye opening or response to verbal command) and extubation time (defined as the time from the completion of operation to extubation) was evaluated and recorded. Objective pain score (OPS) (as shown in Table 1) [22,23] was used for the evaluation of pain degree, and the PAED scale (as shown in Table 2) [2427] and CPS (as shown in Table 3) [2830] was employed to assess POED at the time points of 0, 5, 15, 30, 45, and 60 minutes after transfer into the PACU. One parent or guardian met the child on arrival in the recovery area and the child was allowed to regain consciousness undisturbed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 1–2 µg/kg intranasal dexmedetomidine was found to attenuate the stress response caused by intubation in children [124]. Premedication with intranasal dexmedetomidine also reduced the minimum alveolar concentration of sevoflurane needed for laryngeal mask insertion or tracheal intubation [82, 125, 126]. …”
Section: New Clinical Applicationsmentioning
confidence: 99%
“…Our sample size estimation was based on the incidence of ED in children who received preoperative intranasal dexmedetomidine and in children who received only saline solution [16] In total, 27 patients were required in each group to detect a 45% difference in the incidence of ED between the groups with a statistical power of 90% and a type I error α equal to 1%. Considering a dropout rate of 20%, the minimum number of patients to include was increased to 34 per group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this molecule acts in the locus coeruleus determining a sedation pattern similar to natural sleep, without determining respiratory depression [12][13][14]. Recent studies suggest, among the remedies against ED, the use of dexmedetomidine intranasally as a premedication [10,11,15,16]. In particular, a recent meta-analysis showed that intranasal dexmedetomidine provides more satisfactory sedation and reduces the need for rescue analgesics and the incidence of nasal irritation and postoperative nausea and vomiting compared with other premedication treatments [10].…”
Section: Introductionmentioning
confidence: 99%